外来で利用できる看護記録の提案 - 甲斐 仁美; 桜井 礼子; 藤内 美保; 草間 朋子 (看護科学研究, 2010)
We conducted the qualitative inductive research in order to analyze the process of pain assessment. We indicated that process of pain assessment consisted of four stages. Based on the result, we developed the draft of a fill-out form for acute pain assessment and applied it to 61 patients to complete the draft form in an outpatient clinic that had the emergency care unit. Questionnaire survey and the interview were also conducted to evaluate the availability of the assessment form. Over 80% of the nurses responded positively in terms of the effectiveness of the form. It was found that the assessment form can make diagnosis of acute pain with accuracy and also make prediction of the related disease in a short time by paying attention to acute pain. It was suggested that the form was also useful for the nursing staff to smoothly make decisions at each level of nursing assessment. In addition, it was effective that some nurses realize significance of nursing record. The time required to fill in the form was about 6 minutes on the average and the available information based on the filled form may be helpful as nursing record which was compatible with other nursing staff to promote continuous nursing with speed and accuracy. This study suggested that the draft form for assessment of acute pain was in particular, practical to assess the acute pains of outpatients to whom nursing record system was not fully equipped yet. 外来看護師を対象にした質的帰納的研究により痛みのアセスメント過程を4段階に分析し、その結果に基づき試作した「急性の痛みの記録用紙」を61例の患者に試用し、試用結果をもとにして外来看護の記録用紙を完成させた。試作した記録用紙に関する改善点等の意見を質問紙およびインタビューにて把握した。本論文では、試作した記録用紙の試用の結果と試作記録用紙の主な改善点について報告する。試用した看護師の80%以上が試作した記録用紙は使いやすいと回答した。また、記録用紙の試用により、看護記録の必要性、看護師独自の判断の必要性、継続看護および看護記録による情報の共有化の必要性などを認識したと回答し、看護師自身の意識に変革がみられた。記録用紙を用いることにより、急性の痛みを平均6分で的確にアセスメントすることができ、継続看護および情報の共有化のための看護記録としても有用であることが示唆された。記録用紙の順序に従いアセスメントすることで、短時間で痛みの的確な判断や疾患の予測もできることが明らかとなった。